Determination of the antidepressant fluoxetine in human plasma by LC with UV detection - Maya, MT (2015)
A selective and sensitive isocratic high-performance liquid chromatographic (HPLC) method was developed for the quantitative analysis of low concentrations of fluoxetine (FLX) in human plasma, with ultra-violet detection at 226 nm. A reversed-phase column, LiChrospher((R)) 60 RP-Select B (125 x 3 mm i.d., 5 mum) (Merck), was used to resolve FLX and diazepam (DZP) (internal standard) from endogenous matrix interferences. FLX was isolated from plasma by liquid-liquid extraction. Two identical HPLC systems were used, both validated under the same study conditions. Each chromatographic separation was completed in 30 min and the results showed a mean relative recovery of 101 and 99.3% and an overall precision (RSD%) of 4.78 and 6.09 for each HPLC system. The standard curve was linear for FLX concentrations over the range of 5.00-50.0 ng ml(-1) (R = 0.997 and 0.998).The limit of quantitation of FLX was 5 ng ml(-1) for both HPLC systems. The method described was applied to the analysis of plasma samples obtained from healthy subjects treated with one single oral dose of 40 mg of fluoxetine. (C) 2000 Elsevier Science B.V. All rights reserved.